Komitmen Reduksi Emisi Karbondioksida (CO2) Tiongkok Sektor Energi berdasarkan Perjanjian Paris, 2016—2020 - Sulistiyono; Indra Jaya Wiranata; Hasbi Sidik (Terekam Jejak Publisher, 2024)
China contributed 27% of global greenhouse gas emissions in 2021. Specifically, the CO2 produced by China contributed 30% of global emissions and made China the largest CO2 emitting country in the world. CO2 emissions produced in the energy sector in 2019 were quite large, namely around 10.62 GtCO2. With China's participation in the Paris Agreement, there is hope for all stakeholders in the success of mitigating world climate change. This research uses a qualitative descriptive approach to analyze China's commitment to reducing CO2 emissions in the energy sector based on the Paris Agreement. This research uses literature study techniques with data condensation, data reduction and data triangulation methods. The conclusion is drawn using the concept of international regime and compliance theory. The results of this research found that China's CO2 emissions in the energy sector continued to increase during the 2016-2020 period. This is because coal-fired electricity generation in China increased by 1.7% or 77 terawatt-hours in 2020. In addition, there was an increase in China's thermal power by 18% from 2016-2020. However, there is also China's success in increasing the percentage of renewable energy capacity from only 13% in 2016 to 15.9% in 2020. This meets the target of China's 13th Five Year Plan which targets an increase of 15% in 2020.